Does corporate social responsibility have impact in corporate reputation?:an analysis of EDP - Santos, Maria João (2011)
Purpose: This paper has one main purpose: to understand the effect of Corporate Social Responsibility (CSR) initiatives developed by EDP Group in its Reputation. By understanding the motivations and results of CSR and their relation with Corporate Reputation (CR), it is intended to compare the external perspective of consumers with internal perspective of employees. Methodology: A quantitative research was employed in this study. Primary data was collected via a questionnaire sent to a mailing list of EDP consumers and a list of EDP employees. Meta analysis used 174 complete responses of EDP consumers and 88 complete responses from EDP employees. Findings: Results show that initiatives in CSR have influence in Reputation of EDP, essentially based on improve stakeholder engagement as a benefit of CSR initiatives. There are some differences between internal and external stakeholders, on which employees value more all CSR results as a sign of CR than consumers. Practical implications: The results could be applied for EDP in its operational strategy, confronting strengths and weaknesses of its action in this field. Limitations: Results may be affected by the idiosyncrasies of surveys, related to both consumers and employees (for instance, due to the fact that selected employees are already participants of volunteering initiatives). The mistrust clime in which this study was developed could also influence results.